2018
DOI: 10.1186/s12911-018-0699-2
|View full text |Cite
|
Sign up to set email alerts
|

Combination of conditional random field with a rule based method in the extraction of PICO elements

Abstract: BackgroundExtracting primary care information in terms of Patient/Problem, Intervention, Comparison and Outcome, known as PICO elements, is difficult as the volume of medical information expands and the health semantics is complex to capture it from unstructured information. The combination of the machine learning methods (MLMs) with rule based methods (RBMs) could facilitate and improve the PICO extraction. This paper studies the PICO elements extraction methods. The goal is to combine the MLMs with the RBMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Eight publications (15%) use rule-bases alone, while the rest of the publications use them in combination with other classifiers (data shown in Underlying data: Appendix A 86 ). Although used more frequently in the past, the five publications published between 2017 and now that use this approach combine it with conditional random fields (CRF), 24 use it alone, 25,26 use it with SVM 27 or use it with other binary classifiers. 28 In practice, these systems use rule-bases in the form of hand-crafted lists to identify candidate phrases for amount entities such as sample size 25,28 or to refine a result obtained by a machine-learning classifier on the entity level (e.g., instances where a specific intervention or outcome is extracted from a sentence).…”
Section: Automation Approaches Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight publications (15%) use rule-bases alone, while the rest of the publications use them in combination with other classifiers (data shown in Underlying data: Appendix A 86 ). Although used more frequently in the past, the five publications published between 2017 and now that use this approach combine it with conditional random fields (CRF), 24 use it alone, 25,26 use it with SVM 27 or use it with other binary classifiers. 28 In practice, these systems use rule-bases in the form of hand-crafted lists to identify candidate phrases for amount entities such as sample size 25,28 or to refine a result obtained by a machine-learning classifier on the entity level (e.g., instances where a specific intervention or outcome is extracted from a sentence).…”
Section: Automation Approaches Usedmentioning
confidence: 99%
“…28 In practice, these systems use rule-bases in the form of hand-crafted lists to identify candidate phrases for amount entities such as sample size 25,28 or to refine a result obtained by a machine-learning classifier on the entity level (e.g., instances where a specific intervention or outcome is extracted from a sentence). 24 Embedding and neural architectures are increasingly being used in literature from the past five years. In the 'Other' category, tools mentioned were mostly other classifiers such as maximum entropy classifiers (n = 3), kLog, J48, and various position or document-length classification algorithms.…”
Section: Automation Approaches Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…PICO framework was used to form clinical queries and facilitate the literature search [ 36 ] ( Table 1 ). Relevant keywords were identified through a primary search on PubMed and Chinese Biological Medicine (CBM) to build the search strategies.…”
Section: Methodsmentioning
confidence: 99%
“…During the search procedure, sensitivity (recall) and accuracy (positive predictive value) are often used to evaluate the search results [41] . A number of researchers have found that the sensitivity (recall) of the P and I in the PICOS-based element search in SR/MA abstracts of clinical trials were 37-84% and 26-80%, respectively [42][43] . In addition, it has been shown that the sensitivity (recall) of P, I, and O were 62%, 47%, and 75%, respectively [47] when using an entity recognition model tool to analyze 191 biomedical articles.…”
Section: Problematic Formulation Of Search Strategies and Implementation Of Search Processesmentioning
confidence: 99%